Charakter i miejsce demografii we współczesnej nauce - Pavlík, Zdeněk (Wydział Prawa i Administracji UAM, 1981)
Demography originated by reason of development of empirical approach in science and it has been closely connected with statistical methods from the very beginning. A strong position of methodology in demography and poorly developed demographic theory are explained by that. The process of demographic study starts in contradistinction to many other empirical domains from preparation of demography subject with the aid of statistical description and only then it comes to its closer examination. A basic part of information about reality vanishes in the preparation process and an important position of demographic analysis in demography is explained by that. From the point of view of development principle — on which hither to existing science classifications are based — demography places itself on a border-line between natural and social domains. This principle is, however, insufficient so it is necessary to complete it with complexity principle. Demography can be judged as a rudimental domain that occupies itself with reproduction of human populations as a resulting process as well as with most important factory bs which this process is influenced. In the same way as each other empirical domain demography can be internally divided according to a criterion: complex-fragmentary, real-abstract, general, -detailed, into four basic sub-domains (Fig. 3): population demography, demographic analysis, theory and methodology of demography. Demography is extensively connected with other empirical domains in the frames of science. These domains deal with other aspects of human existence, human populations and society. It is also connected with methodological domains and the Marxist and Lenin philosophy. The demography experience finds its use in economic and social planning and it is a basis of population policy as a part of social policy.
Features and Place of Demography Within the Frames of Contemporary Science